How History Shaped the Innovator's Dilemma. Issue 1 (2021) - Nicholas, Tom
Abstract : In 1993, four years prior to the publication of Clayton Christensen's highly influential book, The Innovator's Dilemma, the Business History Review published an article by Christensen titled "The Rigid Disk Drive Industry: A History of Commercial and Technological Turbulence." The article relates the theory of disruptive innovation to Alfred D. Chandler's work on large vertically integrated enterprises. It was published during a pivotal era of scholarship on innovation, management practice, and industry evolution, much of which used the history of firms, industries, and technologies to build theory. I survey the impact and critiques of Christensen's research agenda, highlighting how it illustrates where the boundaries associated with the "lessons of history" should be drawn.